Characterization of the cross-lamellar structure of Olivancillaria urceus (Gastropoda: Olividae) and its dissolution pattern. (March 2023) - Limeira Jr, Silvio C.M.; Rodrigues, Sabrina C.; Ghilardi, Renato P.
Abstract: In this work, we sought to characterize the cross-lamellar microstructure of the gastropod Olivancillaria urceus (Röding, 1798) and its profile after immersion in acid medium. For crystallographic analysis, segments of the valve were removed and crushed. The powder obtained was analyzed using Fourier Transform Infrared Spectroscopy with Attenuated Total Reflectance (FTIR-ATR) and X-ray Diffractometry (XRD) techniques. For microstructural analysis, eight sections were taken from the shell using a rotary saw. The face of interest of each section was polished with Saint Gobain silicon carbide abrasive powder with mesh sizes of 320, 500, 600, and 1000. The eight sections were divided into four groups of two samples. Three groups were left in 4 % glacial acetic acid solution diluted in water for intervals of 20, 40, and 60 min, respectively, and the control group was not degraded. All wafers were then analyzed in Scanning Electron Microscopy to ascertain the microstructure. The angle and thickness of the layers were determined by Image J software. As a result of the FTIR-ATR technique, a transmittance spectrum was obtained whose valleys represent the vibrational modes of the carbonate ion. The diffractogram peaks and their respective Miller indices, are characteristic of the aragonite crystallographic structure and a small fraction of calcite. The micrographs obtained exposed 3 layers of cross-lamellar microstructure, however, the third and innermost layer showed discontinuity. The angle and average thickness were (105 ± 2)° and (727 ± 5)µm for the outermost layer and (116 ± 3)° and (668 ± 6)µm for the middle layer. The tablets immersed in acid medium showed loss of orientation of the calcium carbonate grains after 40 min and 60 min. Thus, the O. urceus shell exhibits orthorhombic calcium carbonate crystallography. Three layers of cross-lamellar microstructure were identified, as well as the configuration of the structure after contact with corrosive media. These results contribute to the characterization of natural materials and serve as a basis for analysis of the preservation potential in the fossil record. Highlights: The shell of Olivancillaria urceus consists of orthorhombic calcium carbonate. Olivancillaria urceus presents three layers of cross-lamellar microstructure. The third and more internal layer presents discontinuity. In contact with acid medium, the lower order lamellae lose orientation.